Comparison between DySc2N@C80 and Dy2ScN@C80 single-molecule magnetic metallofullerenes encapsulated in single-wall carbon nanotubes. Issue 16 (6th April 2022) - Ito, Satoshi; Nakanishi, Ryo; Katoh, Keiichi; Breedlove, Brian K.; Sato, Tetsu; Li, Zhao-Yang; Horii, Yoji; Wakizaka, Masanori; Yamashita, Masahiro
Abstract : The quantum tunneling mechanism of DySc2 N@C80 and Dy2 ScN@C80 in single-walled carbon nanotubes was revealed to be tuned in opposite ways. Abstract : Encapsulation of a metallofullerene single-molecule magnet, Dy2 ScN@C80, into single-wall carbon nanotubes (SWCNTs) accelerates magnetic relaxation processes. In contrast, encapsulation of DySc2 N@C80 suppresses them. The effects of the encapsulation are discussed in terms of intermolecular magnetic interactions and charge transfer among metallofullerenes and SWCNTs.